Investigation with Employees - بيداء أبراهيم قادر (Journal of Madenat Alelem University College, 2012)
Legislations are usually keen to ensure a kind of guarantees which emphasize the management’s commitment to the principle of legitimacy, not using the power abusively, excessively, or for personal purposes so as to preserve the employee’s rights. Accordingly, most disciplinary laws provide that it is not permissible to punish the employee before interrogating, listening to, giving him the chance to defend himself, and recording all that in a legal record. These laws also necessitate that the disciplinary decision should have a cause and it is not permissible to sign more than one penalty for one violation. Thus, investigation is the management means to take legal actions against the employee when he does an action constituting a violation of public work regulations, and it is a preliminary procedure aiming at discovering the truth about the accused and the charge attributed to him. We have tackled the topic of investigation due to its great importance as one of the guarantees which ensure the employee’s stability and his social security in getting a job and keeping it, receiving a promotion, and gaining the social value and thus being protected from management abuse.